Renal cell carcinomas mass of <4 cm are not always indolent - Nessn H Azawi; Lars Lund; Mikkel Fode (Urology Annals, 2017)
Context: The rate of progression to metastatic disease in patients undergoing active surveillance for small renal tumors varies in the literature between 1% and 8%. Aims: This study aims to examine the incidence of metastasis in small renal tumors of <4 cm in a Danish cohort. Settings and Design: Retrospective. Methods and Material: Data on 106 patients who were diagnosed with renal cancer (RCC) of <4 cm by CT scan from January 2005 to December 2013 were collected retrospectively in January 2016 from patient charts and analyzed. Statistical Analysis Used: The cancer-specific survival (CSS) and overall survival (OS) were estimated using Kaplan-Meier methods. Results: The mean age was 62 years (range 40–84 years). Two patients (1.9%) had metastases at the time of diagnosis. Radical nephrectomy was performed in 74 patients (70%); of them, one patients (1.4%) experienced late metastasis (LM). Partial nephrectomy was performed in 30 patients (28%); of them, two patients (6.7%) experienced LM. The mean time to LM was 27 ± 12 months (95% confidence interval: 4–56). CSS rates were 98%, 97%, and 97% for 1, 3, and 5 years, respectively, while OS rates were 96%, 92%, and 86% for 1, 3, and 5 years, respectively. On multivariate analysis, tumor size (P = 0.04), pT3a (P = 0.0017), and patient's age (P = 0.02) at the time of diagnosis were significant predictors of LM. Conclusions: Even small renal carcinomas may be aggressive, and caution should be taken when offering active surveillance.